Martin Luther, die Juden, der Nationalsozialismus – Kritische Nachlese zum Reformationsjubiläum - Retter, Hein (International Dialogues on Education Journal, 2017)
The article informs and reflects on the results of two conferences in the context of the Reformation Jubilee, which dealt with Martin Luther’s relationship with the Jews. In the background is the question of the impact of Luther’s anti-Jewish hostility as the basis of legitimation for anti-Semitism from the 16th century until the genocide of Jews in Europe by National Socialism.